ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU KAYU PADA UD. SAHIDA MEBEL, DI KECAMATAN SANGGALANGI KABUPATEN TORAJA UTARA - Antonius Bussan; Dwibin Kannapadang; Grace Sriati Mengga (ITB AAS Indonesia Surakarta, 2025)
Every trading business always requires an inventory of raw materials. Without having inventory, the company will face risks such as delays in the production process and not being able to meet consumer demand on time due to a shortage of raw materials. This can happen because raw materials are not available at any time, which means the company will lose the opportunity to gain the profits it should get. Therefore, the company must have an inventory management strategy in which the company must ensure that it is able to provide supplies with quality, quantity and on time. Therefore UD. Sahida Mebel must pay attention to the amount of inventory in order to meet consumer demand, using the Just In Time method approach. This research aims to evaluate an inventory system that can minimize inventory and inventory costs by comparing the current inventory system with the Just In Time method. The minimum inventory and inventory costs using the Just In Time method are more economical, namely 2 m3 and Idr 4,000,000, while the minimum inventory and inventory costs using the method applied by the company are 3 m3 and Idr 5,000,000. From these results, it is known that Just In Time is more efficient to use. Keywords: Just In Time; raw material inventory; minimum inventory; and cost savings